Cost-effectiveness analysis of COVID-19 booster vaccination with BNT162b2 in Japan - Mitsuhiro Nagano; Kazumasa Kamei; Hiroyuki Matsuda; Chihiro Takahashi; Jingyan Yang; Koji Wada; Naohiro Yonemoto (Taylor & Francis Group, 2024)
ABSTRACTBackground The aim of this study was to evaluate the public health and economic impact of the COVID-19 booster vaccination with BNT162b2 in Japan during an Omicron-dominant period from early 2022.Research design and methods A combined cohort Markov decision tree model estimated the cost-effectiveness of annual or biannual booster vaccination strategies compared to no booster vaccination for those aged 65 years and above, and those aged 60-64 years at high risk as the base case. The societal perspective was primarily considered. We also examined other target populations with different age and risk groups. Sensitivity and scenario analyses with alternative inputs were performed.Results Annual and biannual vaccination strategies were dominant from the societal perspective in the base case. Incremental Cost Effectiveness Ratios (ICERs) from the payer perspective were JPY 1,752,499/Quality Adjusted Life Year (QALY) for annual vaccination and JPY 2,831,878/QALY for biannual vaccination, both less than the threshold value in Japan (JPY 5 million/QALY). The results were consistent even when examining other target age and risk groups. All sensitivity and scenario analyses indicated that ICERs were below JPY 5 million/QALY.Conclusions Booster vaccination with the COVID-19 vaccine BNT162b2 is a dominant strategy and beneficial to public health in Japan.